Supercritical fluid extraction of grape seeds: extract chemical composition, antioxidant activity and inhibition of nitrite production in LPS-stimulated Raw 264.7 cells. Issue 8 (5th August 2015) - Pérez, Concepción; Ruiz del Castillo, María Luisa; Gil, Carmen; Blanch, Gracia Patricia; Flores, Gema
<x xml:space="preserve">Abstract</x> Grape by-products are a rich source of bioactive compounds having broad medicinal properties, but are usually wasted from juice/wine processing industries.